2018
DOI: 10.12911/22998993/92889
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Macroelements from Municipal Sewage Sludge by the Multiflora Rose and the Virginia fanpetals

Abstract: Municipal sewage sludge contains many valuable nutrients which can be used in the cultivation of energy crops. Application of large doses of sewage sludge can be a cause of environmental pollution, especially with nutrients. The multiflora rose and the Virginia fanpetals are plants with high nutritional requirements. The use of municipal sewage sludge in the cultivation of energy crops will allow recycling the nutrients from this organic waste. The aim of the study was to evaluate the use of macroelements from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
(40 reference statements)
1
18
1
Order By: Relevance
“…Our research revealed that the lower the dose of sewage sludge, the lower the uptake of macronutrients with the yield of reed canary grass and giant miscanthus biomass. The lower amount of macronutrients uptaken results from the amount of yield and the 'dilution effect' of these nutrients in the plant biomass, which finds confirmation in other studies (Antonkiewicz et al 2018, Berglund et al 2019, Biel et al 2017. The study by Berglund et al (2019) also confirms that reed canary grass utilizes macronutrients well and, compared to other species of grasses, it takes up more of them with the yield compared to the amounts introduced with fertilizers.…”
Section: Macronutrient Uptakesupporting
confidence: 55%
See 3 more Smart Citations
“…Our research revealed that the lower the dose of sewage sludge, the lower the uptake of macronutrients with the yield of reed canary grass and giant miscanthus biomass. The lower amount of macronutrients uptaken results from the amount of yield and the 'dilution effect' of these nutrients in the plant biomass, which finds confirmation in other studies (Antonkiewicz et al 2018, Berglund et al 2019, Biel et al 2017. The study by Berglund et al (2019) also confirms that reed canary grass utilizes macronutrients well and, compared to other species of grasses, it takes up more of them with the yield compared to the amounts introduced with fertilizers.…”
Section: Macronutrient Uptakesupporting
confidence: 55%
“…Only available forms of these nutrients can be taken up by plants (Tkaczyk et al 2017, Symanowicz et al 2018 in the authors' own research presumably resulted from the lower yield, and thereby from a higher 'concentration' of nutrients in the plant biomass. Other authors' studies confirm that plants with higher yields are characterized by the 'dilution effect', hence the lower content of the analyzed elements in the plant biomass can be explained (Antonkiewicz et al 2018, Pogrzeba et al 2018, Witkowicz et al 2015. The value of the concentration index (CI) indicates that reed canary grass took up Na and Ca from sewage sludge more intensely.…”
Section: Macronutrient Contentmentioning
confidence: 92%
See 2 more Smart Citations
“…Detailed information put into agrophysical models may constitute a new quality in research on how crop production will change in the conditions of a changing climate (Pirttioja et al, 2015;Fronzek et al, 2018) and how different cultivation and fertilization methods will impact this production . The balance of NPK also depends on the root system of the plant species and the level of mineral and organic fertilization (Antonkiewicz et al, 2018;Watros et al, 2018). The content of mineral nitrogen in the soil is also impacted by the biological activity of the soil, which in turn may be influenced by soil moisture (Wnuk et al, 2017) or N fertilization (Walkiewicz et al, 2018), and by atmospheric conditions.…”
Section: Introductionmentioning
confidence: 99%